2022
DOI: 10.1155/2022/9773089
|View full text |Cite
|
Sign up to set email alerts
|

Computing Fault‐Tolerant Metric Dimension of Connected Graphs

Abstract: For a connected graph, the concept of metric dimension contributes an important role in computer networking and in the formation of chemical structures. Among the various types of the metric dimensions, the fault-tolerant metric dimension has attained much more attention by the researchers in the last decade. In this study, the mixed fault-tolerant dimension of rooted product of a graph with path graph with reference to a pendant vertex of path graph is determined. In general, the necessary and sufficient cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Specifically, [5] and [6] revealed that the metric dimension of , , , , and are equal to 3, while [7] explored minimizing doubly-resolving sets and strong resolvability of and . In addition, Salman et al [8] analyzed three optimization problems including the strong metric, fault-tolerant as well as the local metric dimension problems and applied them to and families of convex polytopes. Next, due to Simić et al [9] , we present an updated integer linear programming model for the locating-dominating number of graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, [5] and [6] revealed that the metric dimension of , , , , and are equal to 3, while [7] explored minimizing doubly-resolving sets and strong resolvability of and . In addition, Salman et al [8] analyzed three optimization problems including the strong metric, fault-tolerant as well as the local metric dimension problems and applied them to and families of convex polytopes. Next, due to Simić et al [9] , we present an updated integer linear programming model for the locating-dominating number of graphs.…”
Section: Introductionmentioning
confidence: 99%